2016
DOI: 10.1111/edt.12297
|View full text |Cite
|
Sign up to set email alerts
|

Cvek pulpotomy – revisited

Abstract: Background/Aim While some studies support the notion that the time elapsed from coronal fracture and treatment with Cvek pulpotomy in permanent teeth plays an important role in minimizing the possibility of pain and discomfort, microbial pulp invasion, and ensuring pulp and periodontal healing, others consider that neither time between the accident and treatment nor size of exposure is critical if the inflamed superficial pulp tissue is amputated to the level of a healthy pulp. This study compares published da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 27 publications
(70 reference statements)
2
34
0
12
Order By: Relevance
“…Despite these guidelines, their use for cFPM in amongst dental care professionals appears to remain limited . Partial and coronal pulpotomies are endodontic techniques that have shown to be successful in immature anterior teeth in children and adults . Coronal pulpotomies have good success rates in permanent posterior teeth with closed apices in adults .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these guidelines, their use for cFPM in amongst dental care professionals appears to remain limited . Partial and coronal pulpotomies are endodontic techniques that have shown to be successful in immature anterior teeth in children and adults . Coronal pulpotomies have good success rates in permanent posterior teeth with closed apices in adults .…”
Section: Introductionmentioning
confidence: 99%
“…If the pulp examined is considered vital, a pulpotomy procedure involving partial removal (2 mm) of the pulp tissue using a sterile diamond bur housed in a high speed hand piece A B followed by the application of a pulp dressing prior to restoration is usually performed. 10 Furthermore, a partial pulpotomy might be advisable in cases of young patients with complicated trauma involving exposure larger than 1 mm or/and occurring within 48 hours of therapy. [6][7][8][9][10] Because the treatment includes surgical removal of soft tissue and preparation of the hard dental structure, the research investigated laser-assisted partial pulpotomy as an atraumatic and aseptic technique which represents an alternative to conventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, a partial pulpotomy might be advisable in cases of young patients with complicated trauma involving exposure larger than 1 mm or/and occurring within 48 hours of therapy. [6][7][8][9][10] Because the treatment includes surgical removal of soft tissue and preparation of the hard dental structure, the research investigated laser-assisted partial pulpotomy as an atraumatic and aseptic technique which represents an alternative to conventional procedures. The majority of the clinical studies reported in the literature highlight the laser coagulation procedure relating to mechanically-exposed pulp during the removal of caries.…”
Section: Discussionmentioning
confidence: 99%
“…The use of other alternatives, such as bioceramic-based cements, has been reported (10). A good restoration that prevents bacterial penetration into the tooth is essential for the success of partial pulpotomy (16). Regaining the normal shape and function of a crown severed with a complicated fracture is challenging.…”
Section: Discussionmentioning
confidence: 99%